The enigma of squamous cell carcinoma of the colon: a case report and review - Oza, Eesha; Rateshwar, Yashvi; Nayyer, Areeba; Brower, Steven (Frontiers in Oncology, 2026)
IntroductionPrimary squamous cell carcinoma (SCC) of the colon is an exceptionally rare malignancy (<1% of colorectal cancers). Its infrequency has limited the development of standardized diagnostic and therapeutic guidelines; most evidence derives from individual case reports. Early recognition is challenging because clinical presentation often mimics more common colorectal tumors.Case PresentationWe describe a 72−year−old woman diagnosed with left−sided (sigmoid) SCC presenting with locally advanced pT4 disease who achieved >12 years of disease−free survival following left hemicolectomy and adjuvant modified FOLFOX−6 chemotherapy. To contextualize this case, we conducted a comprehensive review of 62 published reports meeting strict inclusion criteria. Most patients presented with nonspecific abdominal symptoms. Contrast−enhanced CT(Computed Tomography) and PET/CT (Positron Emission Tomography) were routinely used to define local disease and exclude other squamous primaries. Immunohistochemistry consistently demonstrated positivity for squamous markers (p63, p40, CK5/6) with relative absence of adenocarcinoma-associated markers (CK20, CDX2). Surgery was the primary treatment modality, while systemic chemotherapy was increasingly utilized in stage II–IV disease.ConclusionAdjuvant chemotherapy may benefit select high−risk stage II patients with primary colonic SCC with high-risk features such as pT4 tumor penetration. as exemplified in this case. Consistent data collection, collaboration, and molecular characterization are essential to establish evidence−based treatment strategies for this uncommon malignancy.